COMPUTATIONAL SIMULATION OF THE INTERACTION AMONG AUTOREGULATION MECHANISMS REGULATING CEREBRAL BLOOD FLOW RATE IN SYSTOLIC HEART FAILURE - Bozkurt, Surhan; Ayten, Umut Engin (WORLD SCIENTIFIC PUBL CO PTE LTD, 2023)
In this study, a lumped parameter model which includes systemic circulation, cerebral blood vessels, systemic arteriolar resistance control, heart rate control, cerebral autoregulation mechanisms and cerebral CO2 reactivity was developed to simulate healthy and heart failure conditions. In the healthy cardiovascular system model, the results were obtained with all control mechanisms connected to the model. Whilst heart failure cases were simulated, all control mechanisms were removed from the model. Then, cerebral autoregulation and cerebral CO2 reactivity mechanisms were connected to the model. Lastly, systemic arteriolar resistance and heart rate control mechanisms were connected to the model. Also, Monte Carlo Analysis was performed to determine the range of parameters controlled for simulations of healthy and heart failure conditions. The results showed that blood flow rate in cerebral circulation can be simulated more accurately by modeling interaction among autoregulatory mechanisms rather than studying separately.
Keywords: Mathematical Modeling; Cerebral Autoregulation; Heart Failure; OPHTHALMIC ARTERY; PARAMETER MODEL; SYSTEM; BAROREFLEX; REACTIVITY; RESPONSES; EXERCISE; EXCHANGE; DISEASE; STROKE; Life Sciences & Biomedicine - Other Topics; Mathematical & Computational Biology